Exploring the Role of Departmental Heads in Motivating University Teachers toward Learner-Centered Teaching - Afzal, Dr. Sadia; Bashir, Dr. Samra (ACADEMIA International Journal for Social Sciences, 2024)
The shift toward learner-centered teaching has become a central goal of higher education reform; however, the adoption of constructivist pedagogy remains uneven in many universities of Punjab, Pakistan. Recognizing the pivotal role of academic leadership in facilitating pedagogical change, this study examined how departmental heads motivate university teachers to transition from traditional, teacher-centered approaches to learner-centered teaching. Employing a qualitative research design, data were collected through semi-structured interviews with ten departmental heads working in public sector universities of Punjab. Thematic analysis revealed five major themes: the central role of teachers’ intrinsic motivation, the motivating influence of collaborative professional environments, the importance of guidance-oriented leadership and supportive feedback, the need for meaningful professional development with follow-up, and the role of institutional resources in sustaining innovative teaching practices. The findings indicate that while intrinsic motivation serves as the primary driver of pedagogical change, its sustainability largely depends on leadership practices and institutional support structures. Departmental heads who foster trust, collaboration, mentoring, and practical support create conditions that encourage teachers to engage with learner-centered pedagogy more confidently and consistently. The study concludes that effective motivational leadership, rather than directive supervision, is essential for sustaining pedagogical reform in higher education. The findings offer valuable implications for leadership development, policy formulation, and professional development initiatives aimed at strengthening learner-centered teaching practices in university contexts.